Intelligent Systems Applications in Software Engineering Proceedings of 3rd Computational Methods in Systems and Software 2019, Vol. 1 - Silhavy, Radek; Silhavy, Petr.; Prokopova, Zdenka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents real-world problems and exploratory research that describes novel approaches in software engineering, cybernetics and algorithms in the context of intelligent systems. It constitutes the refereed proceedings of the 3rd Computational Methods in Systems and Software 2019 (CoMeSySo 2019) conference, a groundbreaking online conference that provides an international forum for discussing the latest high-quality research results.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence